General Form of Model-Free Control Law and Convergence Analyzing - Xiuying Li; Guanghui Wang; Zhigang Han (Journal of Control Science and Engineering)
The general form of model-free control law is introduced, and its convergence is analyzed. Firstly, the necessity to improve the basic form of model free control law is explained, and the functional combination method as the approach of improvement is presented. Then, a series of sufficient conditions of convergence are given. The analysis denotes that these conditions can be satisfied easily in the engineering practice.